The Need to Redetermine the Position of ESP Within Educational Setting of Higher Education in Serbia - Stojković, Nadežda; Piršl, Danica (Collection of Papers of the Faculty of Philosophy in Priština, 2018)
English for Specific Purposes (ESP) is present at all Serbian universities, at most faculties (significantly not all), either as an obligatory or less frequently elective course at undergraduate, and sometimes at PhD studies. The subject is usually called English language, yet the content is formed as to follow the major of the faculty and is in truth ESP. However, ESP is nowhere present as a separate course at departments of English Philology. This is a paradox in itself. First, though elements of ESP might be present within other subjects at the philology departments, this is certainly not enough, and still leaves future practitioners without training to manage on their own once they find themselves in a job position that requires knowledge of specialized discourse regarding teaching it. Also, it is a paradox as for a country striving for achieving higher economical status, which implies a two-way communication of professional and scientific expertise necessitated by ESP.